The Role of Work Engagement in Mediating Organizational Culture and Self-Efficacy on Commitment at PT. Perusahaan Listrik Negara - Purnomo; Pranitasari, Diah (Universitas Indo Global Mandiri Palembang, 2024)
Objective: This study aims to determine the influence of organizational culture and self-efficacy on organizational commitment, with work engagement as a mediating variable. Design/Methods/Approach: This research uses a quantitative approach. The population in this study consists of all employees of PT. PLN. The sampling technique used is random sampling, with a sample size of 225 respondents. Data collection was carried out through questionnaires distributed via Google Forms. Data analysis was conducted using SmartPLS 4.0 software to perform outer model tests (convergent validity, discriminant validity, AVE, composite reliability, and Cronbach’s alpha), inner model tests (model fit), and hypothesis testing. Findings: 1) Organizational culture affects organizational commitment, 2) Self-efficacy does not affect organizational commitment, 3) Organizational culture does not affect work engagement, 4) Self-efficacy affects work engagement, 5) Work engagement affects organizational commitment, 6) Organizational culture does not affect organizational commitment through work engagement, 7) Self-efficacy affects organizational commitment through work engagement. Originality/Value: The novelty of this research lies in the fact that no previous studies have examined organizational commitment at PT. PLN by considering the factors of Organizational Culture and Self-Efficacy, with Work Engagement as a mediating variable. Practical/Policy implication: The results of this research can be used as input in formulating human resource policies aimed at enhancing organizational commitment by considering organizational culture, self-efficacy, and work engagement.